2021
DOI: 10.1037/amp0000766
|View full text |Cite
|
Sign up to set email alerts
|

Integrating and synthesizing adversity and resilience knowledge and action: The ICARE model.

Abstract: Adverse childhood experiences affect our bodies, brains, and behavior. Fortunately, decades of developmental science point to nurturing relationships and supportive resources that can counter the negative effects of ACEs. This article presents a model that incorporates developmental, clinical, public health, and biological science and describes potential developmental trajectories of both risk and resilience resulting from early life experiences. Interventions that promote resilience and recovery are described. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 104 publications
1
34
0
1
Order By: Relevance
“…In sum, in support of similar calls to action (Auerbach & Miller, 2018 ; Hawkins et al, 2012 ; Hays-Grudo et al, 2021 ), our findings offer the key implication that state public health agencies should emphasize strategies that focus on tracking and promoting cumulative protective factors among youth. Public health efforts need to focus on maintaining and establishing capacity (internally in public health departments and state public health infrastructure, as well as externally in local communities) to document and disseminate prevalence of multiple protective factors.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In sum, in support of similar calls to action (Auerbach & Miller, 2018 ; Hawkins et al, 2012 ; Hays-Grudo et al, 2021 ), our findings offer the key implication that state public health agencies should emphasize strategies that focus on tracking and promoting cumulative protective factors among youth. Public health efforts need to focus on maintaining and establishing capacity (internally in public health departments and state public health infrastructure, as well as externally in local communities) to document and disseminate prevalence of multiple protective factors.…”
Section: Discussionsupporting
confidence: 74%
“…Another key point of overlap between resilience research and the DAF concerns cumulative protection, that is, the presence of multiple protective factors in an individual's life (Hays-Grudo & Morris, 2020;Hays-Grudo et al, 2021;Sesma et al, 2013;Wright et al, 2013). Research on the DAF consistently shows that the power of assets lies in the cumulative pile-up of effects across multiple contexts (Sesma et al, 2013).…”
Section: Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has shown that resilience is a human strength that may have a considerable impact on subjective well-being or happiness (Lü et al, 2014;Tan et al, 2021). Resilient individuals are more persistent in adverse situations, cope better with everyday difficulties and have more capacity to respond to life stressors (Mandleco and Peery, 2000;Hays-Grudo et al, 2021). Character strengths such as hope, zest, and bravery play an instrumental role in resilience-related factors such as optimism and positive affect (Martínez-Martí and Ruch, 2017), which eventually help resilient individuals face stressors in a positive way.…”
Section: Resilience As Mediator Between Mindfulness and Happinessmentioning
confidence: 99%